Analisa Kinerja Karyawan Bagian Penjualan Produk Electrical dan Mechanical dengan Metode SWOT - Nanda Kharisma; Susanto Susanto; Nur Nawaningtyas Pusparini (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Performance is a performance of the level of success that exists in employees based on the entire process that has been carried out in relation to certain activities during the period determined by the company, especially in the sales sector to achieve turnover for electrical and mechanical products offered to consumers so that further analysis is needed. To further determine the potential performance, use the SWOT method which has 4 parameters such as strengths, weaknesses, opportunities and threats. After carrying out a SWOT analysis, an evaluation of the previously known SWOT conclusions can be determined.